PLX5622 Reduces Disease Severity in Lethal CNS Infection by Off-Target Inhibition of Peripheral Inflammatory Monocyte Production - Spiteri, Alanna G.; Ni, Duan; Ling, Zheng Lung; Macia, Laurence; Campbell, Iain L.; Hofer, Markus J.; King, Nicholas J. C. (Frontiers in Immunology, 2022)
PLX5622 is a CSF-1R inhibitor and microglia-depleting reagent, widely used to investigate the biology of this CNS-resident myeloid population, but the indirect or off-target effects of this agent remain largely unexplored. In a murine model of severe neuroinflammation induced by West Nile virus encephalitis (WNE), we showed PLX5622 efficiently depleted both microglia and a sub-population of border-associated macrophages in the CNS. However, PLX5622 also significantly depleted mature Ly6Chi monocytes in the bone marrow (BM), inhibiting their proliferation and lethal recruitment into the infected brain, reducing neuroinflammation and clinical disease scores. Notably, in addition, BM dendritic cell subsets, pDC and cDC, were depleted differentially in infected and uninfected mice. Confirming its protective effect in WNE, cessation of PLX5622 treatment exacerbated disease scores and was associated with robust repopulation of microglia, rebound BM monopoiesis and markedly increased inflammatory monocyte infiltration into the CNS. Monoclonal anti-CSF-1R antibody blockade late in WNE also impeded monocyte proliferation and recruitment to the brain, suggesting that the protective effect of PLX5622 is via the inhibition of CSF-1R, rather than other kinase targets. Importantly, BrdU incorporation in PLX5622-treated mice, suggest remaining microglia proliferate independently of CSF-1 in WNE. Our study uncovers significantly broader effects of PLX5622 on the myeloid lineage beyond microglia depletion, advising caution in the interpretation of PLX5622 data as microglia-specific. However, this work also strikingly demonstrates the unexpected therapeutic potential of this molecule in CNS viral infection, as well as other monocyte-mediated diseases.